Grazing, social and comfort behaviour of Ankole and crossbred (Ankole × Holstein) heifers on pasture in south western Uganda - Huber, R.; Baumung, R.; Wurzinger, Maria; Semambo, D.K.; Okeyo Mwai, Ally; Winckler, C. (Elsevier, 2008)
The aim of this study was to assess the grazing, social and comfort behaviour of the indigenous purebred Ankole cattle breed and crossbred (Holstein × Ankole) animals under typical management conditions in south western Uganda. Twelve focal animals in each of four groups (two groups per genotype) were observed regarding their grazing, social and comfort behaviour on pasture. No significant differences in grazing behaviour patterns (eating, walking, standing) were found between the genotypes. Resting occurred only very rarely in both genotypes. Walking distances of Ankole and Ankole × Holstein crosses were also similar. There was no difference in the occurrence of agonistic interactions between the two genotypes. However, Ankole cattle engaged in more non-agonistic social interactions than their crossbred counterparts. Individual distances were lower in Ankole heifers and more herd mates were found within a radius of 5 m around the Ankole animals. The most important comfort behaviour pattern in both genotypes was self-licking, which occurred to similar frequency in Ankole and crossbred heifer groups. Crossbred animals scratched themselves and rubbed on objects more often than Ankole heifers. Although Ankole cattle and their Holstein crosses did not differ in grazing, distances walked and agonistic behaviours, the significant differences between the two genotypes in herd cohesion and comfort behaviour may pose challenges on the management of crossbred animals under extensive open grazing conditions as present in south western Uganda. Thus, apart from (re)productive performance traits, behavioural traits of both genotypes may also be taken into account for breeding decisions and management under current production conditions.